Self-regulation in nonlinear dinamic system with inertial excitation - Astrauskienė , E.; Tiknevičienė, Irena; Ragulskis, Liutauras (Lietuvos matematikos rinkinys, 1998)
The motions of investigated mechanisms are principally nonlinear. The analysis of this problem is performed by using the method of two small parameters. The conditions of existence and stability of multiple synchronization regime are obtained.